Get Answers to all your Questions

header-bg qa

If for x\: \epsilon \left ( o,\frac{1}{4} \right )    , the derivative of

  \tan ^{-1}\: \left ( \frac{6x\sqrt{x}}{1-9x^{3}} \right )  is \sqrt{x}\: .g(x)  then g(x) equals :

  • Option 1)


  • Option 2)


  • Option 3)


  • Option 4)



Answers (1)


As we learnt in

Inverse Trigonometric Functions -

The functions \sin ^{-1}x, \cos ^{-1}x, \tan ^{-1}x, \cot ^{-1}x, \csc ^{-1}x and \sec ^{-1}x are the inverse trigonometric functions.

- wherein

If \sin x = \frac{1}{2}

then, x = \sin ^{-1}\frac{1}{2}



Let, \tan^{-1}\:\frac{6x\sqrt x}{1-9x^{3}}=\Theta

\tan \Theta=\frac{6x\sqrt x}{1-9x^{3}}

Differentiating both sidesw.r.t. x we get:

\frac {d \Theta}{d x}\sin^{2}\Theta=\frac{(1-9x^{3})\:9\sqrt x-6x^{\frac{3}{2}}(-27x^{2})}{(1-9x^{3})^{2}}

\frac {d \Theta}{d x}\sin^{2}\Theta=9\sqrt x\:\: \frac{(1+9x^{3})}{(1-9x^{3})^{2}}                ................ ( 1 )

Now, \tan \Theta=\frac{6x\sqrt x}{1-9x^{2}}\:\:\:\Rightarrow \sin^{2}\Theta = 1+\frac{(6x\sqrt x)^{2}}{(1-9x^{3})^{2}}



\sec^{2}\Theta=\frac{(1+9x^{3})^{2}}{(1-9x^{3})^{2}}                            ................... ( 2 )

From ( 1 ) and ( 2 )

\frac{d \Theta}{dx}=\frac{9\sqrt x (1+9x^{3})^{2}}{(1-9x^{3})^{2}}\:\:\frac{(1-9x^{3})^{2}}{(1+9x^{3})^{2}}

\frac{d \Theta}{dx}=\frac{9\sqrt x}{1+9x^{2}}

On comparison, g(x)=\frac{9}{1+9x^{3}}

Option 1)


This option is incorrect.

Option 2)


This option is incorrect.

Option 3)


This option is incorrect.

Option 4)


This option is correct.

Posted by


View full answer

JEE Main high-scoring chapters and topics

Study 40% syllabus and score up to 100% marks in JEE